Host plant resistance to insects - Panda, Niranjan (CAB International in association with the International Rice Research Institute, 1995)
This book presents a broad overview of host plant resistance to insect pests. It shows how plants can defend themselves naturally and how insects have adapted to overcome these mechanisms through coevolution. it also describes screening and breeding for insect resistance. It represents a major advanced textbook for entomologists, plant breeders and all concerned with crop protection